Identifying patients' criteria for assessment of doctors on Polish physician rating websites - Radosław Tymiński; Michał Walczewski; Michał Wieczorek (Journal of Medical Science, 2015)
Introduction. Increasingly popular physician ranking websites have lately become a significant factor in choosing a physician. Aim. The aim of this study was to establish the criteria by which patients assessed doctors on PRWs and which of these criteria were the most crucial during the general assessment of the physicians. Material and methods. Selected narrative comments from two Polish PRWs: znanylekarz.pl and rankinglekarzy.pl were analysed on the basis of the following criteria: kindness and propriety, punctuality, communication with patients, condition and equipment of a doctor's office, length of the appointment, cost of the medical advice. Results. Out of 4375 eligible comments kindness and propriety was assessed most frequently (3012 comments, 68.85%), next was communication, which was evaluated in 2343 comments (53.55%). Amongst the 3012 comments with assessed kindness and propriety, 77.66% (2339 comments) were described positively. In the group of comments with positively evaluated kindness and propriety 2230 comments (95.34 %) were generally positive. Furthermore, communication with patient was assessed in 2343 comments and in 1827 cases (77.98%) the assessment was positive. 1810 comments with positively evaluated communication were generally positive (99.07%). Conclusions. There is a connection between the patients' positive assessment and physician's kindness, personal culture and communication skills; if physicians focus on the aforementioned abilities, it might lead to better physician perception, higher effectiveness of treatment and the lower number of potential law suits.